Prevalence and factors associated with genital chlamydial infections among women attending the gynaecology clinic at Mbarara regional referral hospital. - Musa, Mubiru; Joel, Bazira; Lenard, Abesiga; Joseph, Ngonzi; Ronald, Mayanja; Julius, Mugisha; Innocent, Nkonwa; Andrew, Chakura; Zacharia, Awar; Daniel, Atwine; Musa, Kayondo (Journal of Health, Medicine and Nursing, 2016)
Background: Chlamydia trachomatis is responsible for the most common bacterial sexually transmitted bacterial infection. The largest burden is in low income countries. These organisms are not screened for in Mbarara, and information about the burden of disease is no available. This study aimed at establishing the prevalence and factors associated with genital Chlamydia infection among women of reproductive age attending the gynecology clinic at Mbarara Regional Referral Hospital. Methods: In a cross-sectional study done at Mbarara Regional Referral Hospital, 324 women aged 15-49years were consented and interviewed. Data on socio-demographics, maternal medical conditions, obstetric and gynaecological factors and endocervical swabs were collected consecutively from November 2015 to January 2016 from women attending gynaecology clinic at Mbarara Regional Referral Hospital. Samples were analysed using a using CTK biotech Chlamydia kit, which is a rapid immunoassay test for the detection of genital chlamydial antigen in urogenital samples. Results were analysed using STATA 13, Logistic regression models were used to estimate level of significance, the odds ratios (OR) and 95 % CI of the association between the factors and genital infections. Significance was set at a p value of <0.05. Results: Of the 324 samples collected,86 were positive for C. trachomatis antigen giving a prevalence rate of 26.5%. Of all the associated factors examined, only type of residence was significantly associated with C. trachomatis infection (p= 0.0413) with those living in peri-urban areas at greater risk of infection ( aOR 2.4 95%CI (1.22-4.82). Other social demographic ,medical obstetric and gynecological factors were not associated with C. trachomatis infection. No symptom or clinical sign was significant for the infection. Conclusion and recommendation: The prevalence of genital C. trachomatis infection among women attending gynecology clinic is high. Genital Chlamydia infection has no predictivesigns and symptoms in our setting. Screening of women in reproductive age should be encouraged.
Keywords: Genital Chlamydia trachomatis; Endocervical swabs; Gynaecology clinic.